2016
DOI: 10.1002/casp.2270
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Black Church in HIV Prevention: Exploring Barriers and Best Practices

Abstract: Black people have the highest rate of HIV/AIDS infection in the USA, and they are less likely to access quality physical and mental healthcare. To address these disparities as outlined in the National HIV/AIDS Strategy, there is a need for culturally congruent, innovative approaches to HIV/AIDS prevention. The first multi-denominational national study of Black faith leaders was conducted utilizing focus groups that were held in 11 US cities. The 265 participants were faith leaders who reported involvement in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Thus, their knowledge affected the adoption of prevention practices negatively [ 110 ]. However, analogous to our results, a study on 265 Black faith leaders in the U.S. found that increased awareness regarding HIV through print and social media, church websites, and making policies of HIV prevention could help reduce the disease [ 111 ]. It was further argued that the treatment approach and treatment knowledge were essential role player in preventing the spread of HIV around the world [ 112 ].…”
Section: Discussion Limitations and Future Research Directionssupporting
confidence: 81%
“…Thus, their knowledge affected the adoption of prevention practices negatively [ 110 ]. However, analogous to our results, a study on 265 Black faith leaders in the U.S. found that increased awareness regarding HIV through print and social media, church websites, and making policies of HIV prevention could help reduce the disease [ 111 ]. It was further argued that the treatment approach and treatment knowledge were essential role player in preventing the spread of HIV around the world [ 112 ].…”
Section: Discussion Limitations and Future Research Directionssupporting
confidence: 81%
“…To begin with, the previous studies fundamentally focussed on the prevention and control of diseases such as Malaria, AIDS, 1 West Nile, Dengue, Zika, and Chikungunya ( Cui et al, 2019 ; Omodior et al, 2018 ; Przybyla et al, 2019 ; Raude et al, 2019 ; Xiaoliang et al, 2016 ). The first group of researches focussed on the epidemiology of diseases like Malaria, Dengue, and AIDS ( Bryant-davis et al, 2016 ; Cui et al, 2019 ). The second group of researches was based on surveys and their interpretation through the response rate of certain variables on epidemic prevention ( Baghbanzadeh et al, 2020 ; Sued et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, these churches have helped shape Black Americans’ attitudes on a range of interpersonal and civic issues such as romantic partner selection (Collins & Perry, 2015) and political engagement (McDaniel, Dwidar, & Calderon, 2018). They have also been sites of health education on topics such as cancer (McNeill et al, 2018) and HIV (Bryant-Davis et al, 2016). In addition, many Black churches provide economic resources and supportive networks for their members who face poverty and racial oppression (Barnes, 2015; Butler-Barnes et al, 2018; Lincoln & Mamiya, 1990).…”
mentioning
confidence: 99%